1999
DOI: 10.1021/jo990424f
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Neighboring Group Participation and Ortho Esters in β-Xylosylation:  13C NMR Observation of a Bridging 2-Phenyl-1,3-dioxalenium Ion

Abstract: The role of ortho esters in the formation of 2,3,4-tri-O-benzoyl-β-xylopyranosides from various donor/promoter pairs has been investigated. It is concluded that for the activation of sulfoxides with Tf2O, thioglycosides with PhSOTf, and bromides with AgOTf the anomeric configuration of the donor is of no consequence on the outcome of the reaction. In all methods studied, the presence or absence of a non-nucleophilic, hindered base is of crucial importance with ortho esters only being discernible in its presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 31 publications
6
67
0
1
Order By: Relevance
“…These correlations strongly suggest the bridging dioxalenium ion 41 formed through participation by the neighboring O-2 benzoyl group. The chemical shift of 180.8 ppm for the bridging carbon in 41 was similar to the value of 180.3 ppm observed for the dioxalenium ion 42 formed from xyloside 43 55. The HSQC spectrum of 41 indicated that the anomeric carbon was also downfield shifted to 114.2 ppm (Figure S3).…”
Section: Resultssupporting
confidence: 67%
“…These correlations strongly suggest the bridging dioxalenium ion 41 formed through participation by the neighboring O-2 benzoyl group. The chemical shift of 180.8 ppm for the bridging carbon in 41 was similar to the value of 180.3 ppm observed for the dioxalenium ion 42 formed from xyloside 43 55. The HSQC spectrum of 41 indicated that the anomeric carbon was also downfield shifted to 114.2 ppm (Figure S3).…”
Section: Resultssupporting
confidence: 67%
“…Anomeric substituent ) that was 226-fold faster than the conformationally flexible thioxyloside 30 [36] (k = 8.4 10 À4 s À1 ) at performing glycosylation. In this case, release of steric strain can be excluded as an explanation for the observed effect.…”
Section: Compoundmentioning
confidence: 99%
“…The use of 2-O-benzoyl-glycosyl donors can commonly produce a unique 1,2-trans-glycosidic bond due to the participation of a neighboring group. 10 The glycosyl donors involved in the synthesis are shown in Scheme 2. Glycosyl trichloroacetimidates 1a-6a were readily prepared in good yields from the corresponding 1-OH sugars.…”
Section: Resultsmentioning
confidence: 99%